Improving Performance Through Job Satisfaction in Growing Employee Motivation at BANK BNI Muara Bungo Branch - Osrita Hapsara; Ahmadi Ahmadi (Dinasti Publisher, 2024)
This research focuses on the important role of job satisfaction and employee motivation in enhancing performance at Bank BNI, Muara Bungo Branch. Job satisfaction is described as the difference between the amount of rewards received by employees and the amount they perceive they should receive, while motivation is considered as a reservoir of potential energy dependent on employees' drives, hopes, and incentives. This study employs a descriptive-verification research method with job satisfaction and work motivation as independent variables, performance as the dependent variable, and motivation as the intervening variable. Data were collected from employees of Bank BNI, Muara Bungo Branch, and analyzed using partial least squares (PLS). The results of the study indicate that job satisfaction and employee motivation are at a good and high level. Furthermore, the research reveals that job satisfaction has a significant positive influence on employee motivation, and employee motivation also has a significant positive effect on their performance. Moreover, the study supports the existence of a significant indirect effect, where job satisfaction affects employee performance through motivation. These findings underscore the importance of the leadership role of Bank BNI in paying attention to and enhancing job satisfaction and employee motivation as the company's primary resources. Leaders are expected to understand that job satisfaction and motivation play a crucial role in improving employee performance, thus enabling them to take more efficient steps to ensure leadership success and achieve beneficial outcomes for the company.